IMPLEMENTASI MATAKULIAH KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA - Wahyu Eko Setianingsih; Sitti Halimathus Sahdiyah; Ismat Syauqi; Kamvanh Sisombath (SEGMEN Jurnal Manajemen dan Bisnis, 2010)
Entrepreneurship education is growing in recent years. This can be seen from the many collegesthat have made the subject of entrepreneurship as compulsory subjects that must be taken byevery student. Seeing the rapid increase in interest in entrepreneurship among studentsGraduate UNEJ, this research aims to determine students' ability to implement entrepreneurshipcourse has been taught to enthusiasm entrepreneurship.The results showed that the implementation of the entrepreneurship subjects described throughan understanding variable (X1) and the application of (X2) proved significant effect on variableinterest in entrepreneurship (Y). This is because the understanding of entrepreneurship coursesthat lead students to apply them to generate interest in entrepreneurship among studentsGraduate University of Jember.Keywords: Implementation, Understanding, Application, and interest in entrepreneurship.